Seguimiento de pacientes con isquemia miocárdica sin lesiones coronarias obstructivas - Cuba Rodríguez, Ana Liuvys (2025)
Objective. The presence of coronary lesions of less than 50% in patients with myocardial ischaemia is a common diagnosis in cardiac catheterisation laboratories. The aim of this study was to determine the clinical course of patients with myocardial ischaemia in the absence of obstructive coronary lesions. Materials and methods. A prospective analytical study was conducted in 110 patients of both sexes with documented myocardial ischaemia and coronary lesions of less than 50% on coronary angiography. The follow-up period was three years. Results. The mean age was 64.5 ± 7.2 years, with a predominance of females (57%). The most prevalent risk factors were hypertension (58.2%) and dyslipidaemia (44.5%). In 8.3% of cases, re-hospitalisation was required, with heart failure reported as the leading cause (6.5%). Cardiovascular event-free survival during follow-up was 80%, and was higher in patients without coronary lesions. A higher incidence of cardiovascular events was associated with diabetes mellitus, a family history of ischaemic heart disease, and chronic kidney disease. Conclusions. Patients with myocardial ischaemia in the absence of obstructive coronary lesions experienced adverse events during follow-up, particularly those with diabetes mellitus, a family history of ischaemic heart disease, and chronic kidney disease.